Challenges of COVID-19: Preschool Teachers' Views and Experiences During the Quarantine - Gökhan Güneş; Mehmet Toran (Istanbul Kültür University, 2022)
The purpose of the study is to analyze the evidence gathered from the preschool teachers' experiences during the COVID-19 pandemic quarantine. The study was carried out with 11 teachers who have professional experience ranging between 3 to 19 years from private and public preschools. The study was specified according to criterion sampling strategy under the purposeful sampling method. The data gathered via open-ended questions and the phenomenology method, one of the qualitative research designs, was used. The qualitative content analyses technique was applied for analyzing the data. It was reached remarkable themes about the preschool teachers' pedagogical challenges during the COVID-19 pandemic based on the analysis of data. The themes and their subthemes are as follows: The theme "challenges in the distance education process" contains the sub-themes of children, teachers, and parents, the theme "views about educational policy in new normal" contains the sub-themes of technological infrastructure problems, unpreparedness, and negative attitudes, the theme "expectations for the improvement of distance education" contains the sub-themes of teacher training, effective family involvement activities, and technology-based programs.